Near Circumferential Invasive Proliferative Gelatinous Mass in the Calf: An Unusual Presentation of Hidradenitis Suppurativa - Shih Jia Janice Tan; Hsien Ts'ung Tay (European Medical Journal, 2019)
Hidradenitis suppurativa, or acne inversa, is a chronic, recurrent inflammatory disease of the skin and subcutaneous tissue, and is characterised by painful, recurrent nodules that results in abscesses and formation of chronic draining sinus tracts and scarring. It has been traditionally described as a disease of the apocrine gland. Present evidence, however, suggests it is a disease of the follicular epithelium and the pathogenesis is complex and multifactorial, implicating genetics, microbiome, physiological, and environmental factors. Recently, several cases of apparent hidradenitis suppurativa have been reported in the literature in areas of the body that defy Dessau's typical topographic criteria. Herein, the authors described an unusual case of a 69-year-old female who presented with hidradenitis suppurativa in her calf post-thermal injury. This case will add to the sparse literature on hidradenitis suppurativa in apocrine-devoid sites and lends credence to the argument that the pathogenesis of hidradenitis suppurativa is multifactorial and complex in nature.